2005
DOI: 10.1038/sj.gene.6364222
|View full text |Cite
|
Sign up to set email alerts
|

No association between E- and L-selectin genes and SLE: soluble L-selectin levels do correlate with genotype and a subset in SLE

Abstract: Altered function of selectin glycoprotein adhesion molecules may modulate severity and organ-specific manifestations of autoimmune and inflammatory disease via changes in leukocyte trafficking. Serum concentrations of selectin molecules have been suggested as useful biomarkers in systemic lupus erythematosus (SLE). We identified increased levels of soluble L-selectin (sL-selectin), but not soluble E-selectin (sE-selectin) in 278 European-Caucasian lupus patients compared to 230 healthy siblings (P ¼ 0.002). sL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 46 publications
2
12
0
Order By: Relevance
“…CD62L belongs to a member of selectins that is important for NK cells homing to the lymph nodes and also an important marker for NK maturation and response to viral infections [23]. Previous studies have shown that circulating soluble CD54 and CD62L correlated with SLE disease activity [24, 25]. …”
Section: Introductionmentioning
confidence: 99%
“…CD62L belongs to a member of selectins that is important for NK cells homing to the lymph nodes and also an important marker for NK maturation and response to viral infections [23]. Previous studies have shown that circulating soluble CD54 and CD62L correlated with SLE disease activity [24, 25]. …”
Section: Introductionmentioning
confidence: 99%
“…We have already studied these two genes and found no evidence of association with SLE, although two variants in the EGF domain were associated with the levels of soluble L-Selectin. 9 All three selectin genes are located in a gene cluster on chromosome 1. The selectin molecules begin with an N-terminal, 'lectin' domain followed by an 'EGF' domain, nine tandem consensus repeats similar to those in complement-binding proteins, a transmembrane domain and a cytoplasmic tail.…”
Section: Introductionmentioning
confidence: 99%
“…Even though our sample size was similar to Macías et al 2003 (16 versus 11), we could not confirm this conclusion since the difference did not reach a statistical significance (data not shown). Some researchers have suggested that soluble levels of E-selectin are gender dependent, being higher in men [6871]. To test whether age and gender could be introducing bias in our results, the soluble levels of E-selectin were adjusted by age and gender (Table 3) without any significant evidence ( P > 0.27), reinforcing that higher levels are related with the disease group tested in this study.…”
Section: Resultsmentioning
confidence: 65%